Sejarah Bahasa Melayu : Sulawesi Tengah 1793-1795 - Collin, James T. ([Makassar] : Institut Melayu Antar Negara, Universitas Negeri Makassar ; [Bangi] : Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2006)
History of Malaya Language in Central Sulawesi, 1793-1795
Bibliography: p. 91-100
Keywords: Malay language -- History; Malay language (Indonesian) -- History